Problem Childfree Ditinjau Dari Worldview Islam - Hidayat, Ahmad Agus; Nurhayati, Nurhayati; Al Farabi, Fahmi Akhyar; Nugroho, Allam Setiawan (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
Childfree, as a phenomenon, emerged from Western issues concerning women, such as the rise of feminism, social equality, political campaigns about body autonomy, and so on. The term